Makna Simbolik Tari Salonreng: Ekspresi Budaya dan Pelestarian Warisan di Desa Ara, Indonesia - Reyna Salsabila Akram; Alem Febri Sonni; Muh. Akbar (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2025)
Indonesian traditional dance, as part of cultural heritage, contains deep symbolic values. One interesting example is the Salonreng Dance from Ara Village, South Sulawesi, which reflects the relationship between humans and nature, culture, and spiritual power. Although it plays an important role in the lives of the local community, understanding of the symbolic meaning contained in the movements, music, costumes, and rituals of this dance is still limited. This study aims to explore the symbolic meaning in the Salonreng Dance and its role in strengthening the cultural identity of the Ara Village community. This study uses a qualitative approach with semiotic analysis, specifically Ferdinand de Saussure's theory, to understand the relationship between the signifier and the signified in each dance movement. Data was collected through interviews with key informants, participatory observation, and documentation. The results of the study show that each movement in the Salonreng Dance contains symbolic meanings that reflect local cultural values, such as happiness in marriage, acceptance, and maintaining harmony in the household. In addition, Salonreng Dance also plays an important role in strengthening social relationships and preserving ancestral traditions. The significance of these findings lies in a deeper understanding of the role of dance in maintaining local cultural identity and facing the challenges of globalization. This research also contributes to the preservation of Salonreng Dance as a cultural heritage that must be preserved and passed on to future generations.